LEXICAL STRUCTURE OF MODERN ENGLISH PAREMIAS: A COMPREHENSIVE ANALYSIS - Saydullayeva Surayyo Serajiddinovna (Bright Mind Publishing, 2025)
Paremias, encompassing proverbs, sayings, and idiomatic expressions, are a vital component of linguistic and cultural heritage. This article delves into the lexical structure of modern English paremias, examining their linguistic features, semantic properties, and cultural significance. Through an extensive analysis of selected paremias, this article highlights the intricate lexical patterns and cultural underpinnings of English proverbial expressions.
Keywords: Paremias, cultural significance, moral and ethical themes, semantic properties.